Using Antibiotics Wisely: Education on Correct Use to Prevent the Risk of Resistance in the Community: Bijak Menggunakan Antibiotik: Edukasi Penggunaan Tepat untuk Mencegah Resiko Resistensi di Masyarakat - Devi Ristian Octavia; Risma Ayu Fepbianti; Ajeng Ayu Trisnawati; Ahmad Rizal; Era Lutfiana (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2025)
The lack of public understanding regarding the proper use of antibiotics contributes to the high incidence of antibiotic resistance. This community service activity aims to improve public knowledge about the correct and appropriate use of antibiotics to prevent resistance. The method used includes education and interactive discussions based on the *Active Learning Method for Adults (CBIA)* approach. The education provided covers the definition and function of antibiotics, the concept of resistance, the wise use of antibiotics to prevent the risk of resistance, and mentoring, involving 20 participants from the *PKK (Family Welfare Empowerment) cadre*. Evaluation was conducted using pre-test and post-test questionnaires. The results of the program showed an increase in participants' understanding, exceeding the target (90%). Education followed by interactive discussions has proven to be an effective method in raising public awareness and knowledge about the importance of wise antibiotic use, thereby helping to reduce the risk of antibiotic resistance.